PERSUASÃO E ENGAJAMENTO NO PROCESSO DE APRENDIZAGEM DE LÍNGUA ESPANHOLA MEDIADA POR PERFIS DE ENSINO NO INSTAGRAM - SOUZA, Hayanne Ribeiro de (1999)
The main objective of this study is to analyze how the use of persuasive technologies, created in order to promote the change of behavior of a user, can influence the learning process of an L2 mediated by teaching profiles on the social network Instagram. As specific objectives, this research intends to: Identify the persuasive tools, those created to make a specific behavior easier to be carried out, used by these language teaching profiles to keep learners trapped in the learning process; to verify the impacts of mental triggers (Fogg, 2009) on engagement in teaching profiles; and, also, Understand the user/learner's perspective on learning mediated by teaching profiles. We conducted a qualitative research, of a basic nature, with exploratory purposes, using literature review and documentary procedures, using as data collection tools, observation, screen capture and the digital questionnaire. To this end, we used as a theoretical basis the studies of Fogg (2003) on Persuasion in Captology, understood as the relationship between a persuasive technology and a user with the intention of behavior change by the user, and the Behavioral Model (Fogg, 2009) to understand the performance of mental triggers in behavior changes; the studies on Engagement of Lanier (2018) and Bentes (2019), which consider it as the attempt to keep the user increasingly connected and interacting on the platforms, as well as the studies of Leffa (2012) on language learning. The results obtained indicate that the persuasive technologies, identified in the Instagram platform, fulfill their role since they induce and help the user to achieve the main objective, which is to generate engagement and, consequently, contribute to the learning process of L2, because, by encouraging him to engage the content, it makes the learner spend more time immersed in the universe of the target language, thus increasing the possibilities of meaningful learning.